On estimation of the turbulent mixing layer altitude from the altitude-time distributions of the Richardson number - Banakh, V. A.; Falits, A. V.; Sherstobitov, A. M.; Smalikho, I. N.; Sukharev, A. A.; Gordeev, E. V.; Zaloznaya, I. V (Atmospheric and oceanic optics)
Time series of the turbulent mixing layer altitude derived from the altitude-time distributions of the turbulence kinetic energy dissipation rate and of the gradient Richardson number are compared. We have found that the estimates of the turbulent mixing layer altitude from the altitude-time distributions of the Richardson number and of the turbulence kinetic energy dissipation rate are close only under the conditions of atmospheric boundary layer instability due to convection. In other cases, the mixing layer altitude derived from the Richardson number can be significantly underestimated.